STRATEGI PENGEMBANGAN KUD HANUMAS DI DESA MAYANG SARI KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN - Melinda Yani; Caska Caska; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The purpose of this study was to analyze the internal factor influencing the development of Rural Unit Cooperarives, to analyze the external factor influencing the development of Rural Unit Cooperatives, and to determine the strategy HANUMAS of Rural Unit Cooperatives development in Mayang Sari. Data collection based on interviews and questionnaires. Sampling technique uses purposive sampling totaling 26 respondents. Data analysis used is swot analysis. The results of this study indicate that the strategy applied to HANUMAS of Rural Unit Cooperative activites is strategy (SO) revitalizing cooperativis and expanding the scope of cooperative management, innovating in terms of procedures and mechanisms for Rural Unit Cooperatives and maximizing cooperative business units to attract community interest using village unit cooperative services (ST) socialize and approach the community (WO) develop a village unit cooperative business unit (WT) improvement of management to improve cooperative competitiveness.Key Words: Development Strategy, SWOT anality